HUBUNGAN ANTARA STATUS C-ORGANIK DAN STABILITAS AGGREGAT TANAH KEBUN PERCOBAAN LIMAU MANIS PADANG PADA BEBERAPA PENGGUNAAN LAHAN - Yulnafatmawita Yulnafatmawita (Jurnal Solum, 2006)
Organic matter is one of soil bonding agent in formation and stabilization of soil aggregates or soil structure.  Since it affects several other soil peorperties, soil structure is considered as a determinant for soil quality.  Therefore, depletion of organic matter content in a soil will cause soil degradation and consequently environmental pollution.  This research was aimed to determine org-C status of Ultisols Limau Manis and the relationship to aggregate stability, as affected by land use change.  The results showed that soil organic-C decreased by approximately 42% (from 9.86% to 5.75%) and by 55% (from 9.86% to 4.42%) at 0-10 cm depth and by 45% (from 3.79% to 2.09%) and 18% (from 3.79% to 3.10%) at 10-20 cm depth as land use was changed from forested ecosystem to perennial and annual crops, respectively, in Ultisols Limau Manis Padang.   There was a tendency of positive correlation between soil org-C status and the aggregate stability, or negative correlation between org–C status and the dispersion ratio (DR).  Between both depths, 10-20 cm depth showed a stronger correlation than that of 0-10 cm depth.Key words: org-C, land use change, dispersion ratio, aggregate stability